A damage-plasticity based interface model for simulating in-plane/out-of-plane response of masonry structural panels. (February 2022) - Nie, Yu; Sheikh, Abdul; Griffith, Michael; Visintin, Phillip
Highlights: An interface constitutive model is proposed based on the realistic physical behaviour of mortar joints. Damage evolution is coupled in the plasticity theory for modelling the nonlinear behaviours of interfaces. Sub-stepping scheme helps to improve the computational robustness significantly. Simulating the failure of masonry walls under in-plane and out-of-plane loading conditions. Abstract: A coupled damage-plastic based constitutive model using a traction-separation law is developed in this study to simulate the behaviour of mortar joints in masonry structural panels subjected to in-plane (2D) and out-of-plane (3D) loading. A smooth hyperbolic failure surface is used to develop the interface material model, which is implemented numerically using a fully implicit backward Euler integration technique is unconditionally stable. To further improve the accuracy and robustness of the interface model, an adaptive sub-stepping scheme and associated consistent tangent operator are formulated considering the effects of damage and plastic deformations. This is beneficial for simulating full-scale masonry structures because the size of load step for some locations with higher deformations can be significantly larger than other locations. The model is first validated using a single cohesive element within a finite-element modelling platform, to assess its behaviour under all possible deformation modes: tensile, compressive with shear and tensile-shear mix-mode behaviour. The cyclic response of a masonry couplet is then simulated to assess model performance in the unloading scenario. Finally, the model is applied to masonry structural walls for simulating their failure response under in-plane and out-of-plane loads, and a good correlation with the experimental results is observed.